Opportunities and challenges with the implementation of normothermic machine perfusion in kidney transplantation - Ton J. Rabelink; Sarah Hosgood; Thomas Minor; Markus Selzner; Annemarie Weissenbacher; Henri GD Leuvenink; Stefan Schneeberger (Nature Communications)
Abstract End stage kidney disease and dialysis are lifetime limiting and lifestyle-defining conditions with enormous costs to the health care system. Despite a severe organ shortage, thousands of organs that are retrieved for transplantation go to waste every year because of the presumed inadequacy of organ quality and/or the limited organ preservation time. Normothermic kidney machine perfusion (NMP) holds the potential to resolve this through improved preservation, prolonged preservation time, kidney quality assessment, reconditioning and treatment. We herein develop a perspective on the potential, but also the hurdles towards the breakthrough of this technology.